Quantification of Fat Metaplasia in the Sacroiliac Joints of Patients With Axial Spondyloarthritis by Chemical Shift-Encoded MRI: A Diagnostic Trial - Liu, Dong; Lin, Churong; Liu, Budian; Qi, Jun; Wen, Huiquan; Tu, Liudan; Wei, Qiujing; Kong, Qingcong; Xie, Ya; Gu, Jieruo (Frontiers in Immunology, 2022)
Objective: To study the diagnostic performance of chemical shift-encoded MRI (CSE-MRI) in the diagnosis of axial spondyloarthritis (axSpA). Methods: CSE-MRI images were acquired for consecutive patients complaining of back pain as well as healthy volunteers. Proton density fat fraction (PDFF) values were measured independently by two readers. Diagnostic performance of CSE-MRI was analyzed by ROC curve analysis. Logistic regression analysis was employed to investigate the risk factors of extensive fat deposition in the SIJs. Results: A total of 41 r-axSpA patients, 32 nr-axSpA patients, 23 non-SpA patients and 30 healthy volunteers were included. Mean PDFF values in the SIJs of patients with r-axSpA and nr-axSpA (71.9% and 64.6%) were significantly higher than non-SpA patients and healthy volunteers (57.5% and 56.2%).(p<0.001) By defining extensive fat deposition in the SIJs as ≥8 ROIs with PDFF values over 70%, its sensitivity and specificity in diagnosing axSpA reached 69.85% and 84.50%. By joining bone marrow edema (BME) with ≥8 ROIs (PDFF>70%), 10 (13.7%) and 6 (8.2%) more axSpA patients were classified as SIJ MRI (+) by reader 1 and 2. Multivariate logistic regression analysis confirmed longer disease duration as the independent risk factor of extensive fat deposition in SIJs (OR=1.15, 95%CI[1.01, 1.35]), while bDMARDs medication was a protective factor (OR=0.14, 95%CI[0.03, 0.51]). Conclusion: CSE-MRI is a reliable tool to quantitively assess the fat metaplasia in the SIJs of axSpA patients. CSE-MRI should be included in the routine MR examination for patients suspected of axSpA.